Politik Hukum Tindak Pidana Perpajakan dalam Perspektif Restorative Justice (Mimbar Keadilan, 2023)
The purpose of the study is to analyze the conceptual punishment with the principle of restorative justice in connection with the legal politic of criminal taxation. The method of research conducted in this paper is a normative juridical method. The approach method used in this research is a conceptual approach and a statutory approach. The results of the study concluded that the legal politic of tax crime in the perspective of restorative justice is in the form of expanding the ultimum remedium opportunity which was originally only up to the investigation stage, extended to the trial stage. Furthermore, to promote restorative justice, recovery of losses to state revenues must be prioritized over imprisonment by taking into account: Prosecutor's authority to prosecute; Judge's decision authority; Criminal fines are not subsidized; Authority of Tax Investigators to confiscate assets. From the perspective of restorative justice, recovery of losses to state revenues is prioritized over imprisonment. In solving tax crimes that prioritize restorative justice, it is in line with the government's efforts to increase taxation for the benefit of development. The concept of restorative justice can provide a way out for efforts to increase state revenue from the tax sector.